Massive chest tube output after congenital diaphragmatic hernia repair on extracorporeal membrane oxygenation - Daniel A. Reich; Faidah O. Badru; Moiz M. Mustafa; Saleem Islam (Elsevier, 2023)
Peripherally inserted central catheter (PICC) lines are used routinely in neonates requiring prolonged drugs and parenteral nutrition and complications are usually infectious, mechanical, or thrombotic in nature. Spontaneous extravascular migration is extremely rare, and presentation with large volume chest tube output even rarer. We present a case involving a neonate on extracorporeal membrane oxygenation (ECMO) after congenital diaphragmatic hernia (CDH) repair and discuss management strategies.